STUDI ANALITIK KEKAKUAN ELASTIS PADA METALLIC STEEL DAMPER BERBENTUK X DENGAN SISI LENGKUNG - Deni Hermawan (Jurnal Teknik Sipil USU, 2014)
ABSTRACT Amount of energy subjected to the structure during the earthquake damages the building. Since the last 20 years, a new protection system has been developed to increase safety and reduce the damage in the structure when earthquake occured, it known as seismic device, equipped by active and passive control system. The most practical and suitable method in reducing seismic response in the structure is by using a passive control system. Passive control system based on the procedure of installation consist of viscous damper, viscoelastic damper, friction damper and yielding damper. Yielding Metallic Device is usually known as Metallic Steel Damper. The shape of this device which is often used was damper with X-shaped (ADAS) or V-Shaped (TADAS). Metallic Yielding Damper can be classified into 2 types in restraining shear force from earthquake, those are bending towards strong axis and weak axis. If the installation is towards strong axis, damper will reduce energy of the earthquake through bending mechanism and inelastic shearing. Analytical structure calculation in strong axis for approximately elastic stiffness which will be used without doing an experiment in the laboratory. To determine the elastic stiffness, deflection at damper will be defined by using strain energy method. Both deflection contributed by bending and shear deformation were considered in the analysis. The result of the deflection by using analytical of strain energy method will be compared with experimental results in the laboratory.   Keywords : metallic yielding damper, energy method, Stiffness, deflection